Linking climate change to water provision: greywater treatment by constructed wetlands. (March 2018) - Qomariyah, S; Ramelan, AH; Setyono, P; Sobriyah
Abstract: Climate change has been felt to take place in Indonesia, causing the temperature to increase, additional drought with more moisture evaporates from rivers, lakes, and other bodies of water, and intense rainfall in a shorter rainy season. One of the major concerns is the risk of severe drought leading to water shortages. It will affect water supply and agriculture yields. As a country extremely vulnerable to the climate change, Indonesia must adapt to the serious environmental issues. This paper aims to offer an effort of water provision by recycling and reusing of greywater applying constructed wetland systems. The treated greywater is useful as water provision for non-consumptive uses. A recent experiment was conducted on a household yard using a single horizontal subsurface flow type of constructed wetland. The experiments demonstrated that the constructed wetland systems reduced effectively the pollutants of TSS, BOD, COD, and detergent to the level that are compliant with regulatory standards. The constructed wetland has been established for almost two years however the system still works properly.